Kepemimpinan Dan Gaya Manajemen : Studi Literature - Yusrina Ayu Setiani; Rheza Ray Farandy; Moch. Isa Anshori (International Forum of Researchers and Lecturers, 2023)
Leadership is a classic topic of discussion, but it is very interesting to study because it can be crucial for an organization or company. Organizations or companies involve human interaction, such as the relationship between leaders and subordinates, both of whom work together to complete planned tasks. One of the main responsibilities of a leader is to motivate employees and improve their performance so that they can achieve the goals of the organization they lead. The resources owned by the company will not produce optimal results if they are not supported by human resources who have optimal performance. The purpose of this study is to determine whether leadership style influences job satisfaction through employee motivation and performance. This research uses the type of library research, which is a series of activities related to library data collection methods. The results of this study indicate that leadership, motivation, and job satisfaction are important factors in determining the success and failure of employee performance achievement.